Role of Administration Routes of Anti - Infectious Bursal Disease Virus (Gumboro) Vaccine on Immunization of Chicken - Babiker, M.A.A.; Tawfeeg, E. (International Journal of Poultry Science, 2008)
The aim of the present work was to study the effect of the route of anti-IBDV vaccine administration on elevation of antibody titre and protective efficacy against Gumboro disease in addition the maternally derived antibodies titre (MDA) declining pattern was also studied. For this purpose 125 one day old progeny chicks from a known vaccinated dams were reared at an isolated pens and tested to determine anti IBDV antibody titre at day one (MDA) and day 17. At day 17 birds were divided into 5 groups; A , B, C and D based on the administration route of anti-IBDV vaccine while group E was not vaccinated and acted as negative control. Group A was vaccinated via intranasal (I/N) route. Group B was vaccinated via drinking water (oral) route. Group C was vaccinated via subcutaneous route. Group D was vaccinated via spraying (Inhalation) route. Each group was vaccinated twice at day 17 (Primary) and at day 24 (booster). Fifteen days post booster dose, sera samples were tested and birds were challenged to study the protective efficacy of the vaccine in each group. The mean antibody titre and coefficient of variation of group B were found to be superior to other groups. The protective efficacy parameters including mortality rate, gross lesions grading, bursa to body weight X 10-3 ratio and histopathologic changes grading were found to be better in group B than in other groups.